Labor epidural analgesia and risk of autism Spectrum disorders in offspring: A systematic review and meta-analysis - Fang, Ling-ling; Zhou, Yuan-yue; Jiang, Hai-yin; Shi, Yu-dan (Frontiers in Pediatrics, 2023)
Background: The effect of labor epidural anesthesia (LEA) on the risk of autism spectrum disorder (ASD) in offspring has been investigated recently, and available results are inconsistent. Methods: We searched the PubMed and EMBASE databases for relevant studies and performed a systematic review and meta-analysis of the literature. Subgroup analyses were conducted to assess the sources of heterogeneity. A fixed or random-effects model was used to estimate overall relative risk. Results: Our results showed that LEA was associated with an increased risk of ASD in offspring (HR = 1.3, 95% confidence interval (CI): 1.25–1.35; P < 0.001) after combining crude estimates from the included studies. This association was gradually reduced, but still statistically significant, when the potential confounding factors were considered (HR 1.13, 95% CI 1.03–1.25, P = 0.014). However, there was no significant association when we pooled data of siblings from other pregnancies (HR = 1.07, 95% CI: 0.99–1.16, P = 0.076), implying that the association was due to confounding factors.